Leptospira Infection Interferes with the Prothrombinase Complex Assembly during Experimental Leptospirosis - Vieira, Monica L.; de Andrade, Sonia A.; Morais, Zenaide M.; Vasconcellos, Silvio A.; Dagli, Maria Lucia Z.; Nascimento, Ana Lucia T. O. (Frontiers in Microbiology, 2017)
Leptospirosis is a worldwide zoonotic and neglected infectious disease of human and veterinary concern, caused by pathogenic Leptospira species. Although bleeding is a common symptom of severe leptospirosis, the cause of hemorrhage is not completely understood. In severe infections, modulation of hemostasis by pathogens is an important virulence mechanism, and hemostatic impairments such as coagulation/fibrinolysis dysfunction are frequently observed. Here we analyze the coagulation status of experimentally infected hamsters in an attempt to determine coagulation interferences and the origin of leptospirosis hemorrhagic symptomatology. Hamsters were experimentally infected with L. interrogans. The lungs, kidneys and livers were collected for culture, histopathology and coagulation assays. L. interrogans infection disturbs normal coagulation in the organs of animals. Our results suggest the presence of a thrombin-like factor or FX activator, which is able to activate FII in the leptospirosis organ extracts. The activity of those factors is accelerated in the prothrombinase complex. Additionally, we show for the first time that live leptospires act as a surface for the prothrombinase complex assembly. Our results contribute to the understanding of leptospirosis pathophysiological mechanisms and may open new routes for the discovery of novel treatments in the severe manifestations of the disease.